Mossflower - Jacques, Brian; Chalk, Gary (New York : Firebird, 2002)
Martin the warrior mouse and Gonff the mousethief set out to find the missing ruler of Mossflower, while the other animal inhabitants of the woodland prepare to rebel against the evil wildcat who has seized power.
Prequel to: Redwall.
Keywords: Animals; Fantasy; Science Fiction